2003
DOI: 10.1073/pnas.0737564100
|View full text |Cite
|
Sign up to set email alerts
|

Motion generation by Drosophila mechanosensory neurons

Abstract: In Drosophila melanogaster, hearing is supported by mechanosensory neurons transducing sound-induced vibrations of the antenna. It is shown here that these neurons additionally generate motions that mechanically drive the antenna and tune it to relevant sounds. Motion generation in the Drosophila auditory system is betrayed by the auditory mechanics; the antenna of the fly nonlinearly alters its tuning as stimulus intensity declines and oscillates spontaneously in the absence of sound. The susceptibility of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 33 publications
4
132
0
2
Order By: Relevance
“…The Drosophila auditory organ, Johnston's organ, is situated in the fly's antenna (Fig. 1A) (14)(15)(16)(17). We analyzed the effects of mechanical disruption of the antennal sound receiver on aggressive behavior in two different ways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Drosophila auditory organ, Johnston's organ, is situated in the fly's antenna (Fig. 1A) (14)(15)(16)(17). We analyzed the effects of mechanical disruption of the antennal sound receiver on aggressive behavior in two different ways.…”
Section: Resultsmentioning
confidence: 99%
“…1A) (14)(15)(16)(17). Antennal displacement leads to activation of ∼500 chordotonal stretch-receptor neurons in the JO, which contains AB neurons responsive to sound-evoked vibrations and CE neurons sensitive to sustained antennal deflections caused by gravity and wind (Fig.…”
mentioning
confidence: 99%
“…In O. nigricornis SOs show the same characteristics as SOs in other well characterised insect auditory systems such as Drosophila and mosquitoes (Göpfert and Robert 2001;Göpfert and Robert 2003); they are around the best frequency of the receiver, they increase in amplitude following ethanol injection and they are never seen post mortem. Although their amplitude is in the picometer range, they are observed above the noise floor of the measurement system.…”
Section: Active Auditory Systemmentioning
confidence: 71%
“…To achieve this many animals have evolved a nonlinear auditory response, whereby the receiver shows increased sensitivity to quiet sounds and sensory cells selectively and actively tune into frequencies of interest. Auditory nonlinearities are known across all vertebrate groups (Manley 2000;Manley et al 2008) and in insects have been found in mosquitoes (Göpfert and Robert 2001), Drosophila (Göpfert and Robert 2003) and the tree cricket, O. henryi (Mhatre and Robert 2013). The female O. henryi auditory system becomes selectively tuned into male call frequencies at low amplitudes, but at high stimulus amplitudes this tuning is lost.…”
Section: Introductionmentioning
confidence: 99%
“…8 Sounds are perceived by sensory neurons of Johnston's organ in the second segment of the fly antennae 9,10 and the resonance frequency has been demonstrated to vary in a non-linear manner with sound intensity, thereby improving sensitivity for low song intensities. [11][12][13][14] Courtship of Drosophila consists of a series of different behavioral steps, 4,15,16 initiated by a male's orientation movement towards a female. Tapping of the female abdomen or thorax with one of the forelegs of a male is usually followed by extension of the wing located nearest to the female and the production of a courtship song through rapid vibration.…”
Section: Introductionmentioning
confidence: 99%